2007
DOI: 10.1515/jpm.2007.068
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic QT/RR relationship of cardiac conduction in premature infants treated with low-dose doxapram hydrochloride

Abstract: Doxapram hydrochloride, a respiratory stimulant, has several undesirable side effects during high-dose administration, including second-degree atrioventricular (AV) block and QT prolongation. In Japan, this drug is contraindicated for newborn infants. Recent studies, however, have demonstrated the efficacy and safety of doxapram therapy for apnea of prematurity (AOP) using lower doses than those previously tested. As a result, approximately 60% of Japanese neonatologists continue to use this drug. This study u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 16 publications
0
15
0
1
Order By: Relevance
“…In addition, 130 studies were excluded for the reasons mentioned in figure 1. This left 32 studies for the final analyses, 4 RCTs [13,14,15,16], 1 prospective crossover study [17], 2 case-control studies [18,19], and 25 cohort, case series or case reports studies [20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44]. Four studies were only available in abstract form [19,23,24,38].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, 130 studies were excluded for the reasons mentioned in figure 1. This left 32 studies for the final analyses, 4 RCTs [13,14,15,16], 1 prospective crossover study [17], 2 case-control studies [18,19], and 25 cohort, case series or case reports studies [20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44]. Four studies were only available in abstract form [19,23,24,38].…”
Section: Resultsmentioning
confidence: 99%
“…Sixteen case series were included, reporting a total of 324 preterm infants treated with doxapram (table 1) [27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42]. One study was a pilot study described in a letter to the editor [29], and one study was only available in abstract form [38].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have found that clinical doses of doxapram hydrochloride have no effect on the heart conduction system in rats [5], while doxapram hydrochloride at high doses prolongs the myocardial repolarization interval and causes deterioration of halothane adrenaline-induced arrhythmia. In this study, we focused on doxapram hydrochloride-induced bidirectional ventricular tachycardia (BVT) that is a rare entity occurring in conditions associated with intracellular calcium overload.…”
Section: Introductionmentioning
confidence: 99%
“…Although doxapram can reduce apnea in preterm infants, undesirable side‐effects, such as perforation of the digestive tract, mean that it requires caution at high doses . Recent studies, however, have demonstrated the efficacy and safety of doxapram therapy for AOP at lower doses than those previously tested . The safety and efficacy of respiratory stimulants are important topics in the treatment of AOP.…”
mentioning
confidence: 99%